Development of Learning Management Model Through Participative Reflection to Enhance Critical Thinking of Nursing Students - Chansuvarn, Supattra; Niamhom, Wannee; Srisuantang, Sunti (Journal of Research and Curriculum Development, 2024)
The research aimed to develop a reflective learning model to enhance nursing students' critical thinking skills. The goals were to create the model, evaluate its effectiveness, and monitor the transfer of reflective learning. The study had four phases: identifying problems in reflective learning, developing the model, evaluating its effectiveness, and transferring the learning. The sample group consisted of experts in the field of nursing reflection, teachers responsible for the nursing curriculum, and nursing students. The tools used to collect data were: 1) a questionnaire on current problems regarding students' critical thinking abilities; 2) an assessment of critical thinking ability; 3) an assessment of reflective behavior; and 4) an assessment of satisfaction with learning management. We analyzed the data using mean, standard deviation, T-test, and content analysis. Results: 1. The results revealed that nursing students had problems with critical thinking at a moderate level (= 3.48, standard deviation = 0.56).; as a result, reflective learning should be integrated into the curriculum to enable nursing students to think critically. 2. The development of reflective learning model consisted of five steps: 1) activity preparation; 2) introduction; 3) virtual simulation activity implementation; 4) reflection and learning summary; and 5) evaluation. 3. After the implementation of the model, the nursing students demonstrated discrepancy in critical thinking skills before and after the experiment significantly at the 0.05. 4. The results of the follow-up on the transfer of the reflective learning revealed three key issues: 1) applying the knowledge to patients in real-life situations; 2) solving real problems; and 3) gaining confidence in providing quality patient care. Conclusion: Managing learning through reflection encouraged nursing students to think critically and solve problems in nursing practice.